The Safe Passage Redundancy Analysis of Airport Taxiway Bridge Based on Aircraft Load Fatigue Accumulation - Yuhui Zhang; Yuanyuan Zhao (Applied Sciences, 2023)
This paper is centered around the theoretical, experimental, and simulation analysis of safe passage redundancy and the mechanical deformation of the taxiway bridge under the fatigue accumulation state, and we define the redundancy as the remaining times that the aircraft can pass safely on the taxiway bridge. Based on the principle of stress control, the entity of the taxiway bridge was scaled to establish a laboratory model. The accuracy of the simulation model was verified by the comparative analysis between the experimental and the simulation data. The fatigue–life curve (S–N curve) was introduced to overlay the material fatigue state cycle into the simulation model of the taxiway bridge, and the safe passage redundancy and mechanical deformation of the bridge under the fatigue accumulation state were analyzed. By analyzing and processing the simulation data, a calculation model for the safe passage degree of the taxiway bridge under the fatigue state and a prediction calculation model for the remaining passage life were constructed. By comparing the simulation data with the model data, the accuracy of the established model was verified to be higher than 95%, which provides an important theoretical reference for the development of research on the safety life detection and evaluation of the subsequent taxiway bridge under the fatigue state.